Active MnO2/biochar composite for efficient As(III) removal: Insight into the mechanisms of redox transformation and adsorption. (1st January 2021) - Cuong, Dinh Viet; Wu, Po-Chang; Chen, Lo-I; Hou, Chia-Hung
Highlights: Engineered biochar was decorated with MnO2 as a composite material. As(III) can be oxidized to As(V) and subsequently adsorbed by MBC. pH has a strong effect on arsenic removal due to electrostatic repulsion. Redox transformation plays a crucial role in enhancing the removal of As(III). Graphical abstract: Abstract: In the present work, an active MnO2/rice husk biochar (BC) composite (MBC) was prepared to enhance As(III) removal for groundwater remediation. The MBC material obtained an improved porous structure (i.e., specific surface area, pore volume and mesoporosity) with MnO2, providing abundant reaction or interaction sites for surface or interface-related processes such as redox transformation and adsorption of arsenic. As a result, a significant enhancement in arsenic removal can be achieved by using MBC. More specifically, MBC showed a high removal capacity for As(III), which was tenfold higher than that of BC. This improvement can be ascribed to the redox transformation of As(III) via MnO2, resulting in the more effective removal of As(V) species. In addition, pH was an important factor that could influence the As(III) removal capacity. Under alkaline conditions, the As(III, V) removal capacity of MBC was clearly lower than those under acidic and neutral conditions due to the negative effects of electrostatic repulsion. Importantly, a powerful transformation capability of As(III) via MBC was presented; namely, only 5.9% As(III) remained in solution under neutral conditions. Both MnO2 and the BC substrate contributed to the removal of arsenic by MBC. MnO2 delivered Mn-OH functional groups to generate surface complexes with As(V) produced by As(III) oxidation, while the reduced Mn(II) and As(V) could precipitate on the MBC surface. The BC substrate also provided COOH and OH functional groups for As(III, V) removal by a surface complexation mechanism. Note that the application of MBC in the treatment of simulated groundwater demonstrated an efficient arsenic removal of 94.6% and a concentration of arsenic as low as the 10 µg L –1 WHO guideline.